Association of Regional Variation in Primary Care Physicians' Colorectal Cancer Screening Recommendations with Individual Use of Colorectal Cancer Screening - Jennifer S. Haas, MD, MSPH; Garrett Fitzmaurice, ScD; Phyllis Brawarsky, MPH; Su-Ying Liang, PhD; Robert A. Hiatt, MD, PhD; Carrie N. Klabunde, PhD; Martin L. Brown, PhD; Kathryn A. Phillips, PhD (Centers for Disease Control and Prevention, 2007)
IntroductionStudies show that the recommendations of a primary care physician for colorectal cancer screening may be one important influence on an individual's use of screening. However, another possible influence, the effect of regional differences in physicians' beliefs and recommendations on screening use, has not been assessed.MethodsWe linked data from the National Health Interview Survey on the use of colorectal cancer screening by respondents aged 50 years or older, by hospital-referral region, with data from the Survey of Colorectal Cancer Screening Practices on the colorectal cancer screening recommendations of primary care physicians, by region. Our principal independent variables were the proportion of physicians in a region who recommended screening at age 50 and continuing screening at the recommended frequency.Results On average, 53.3% of physicians in a region correctly recommended initiating colorectal cancer screening, and 64.8% advised screening at the recommended frequency. Of adults who lived in regions where less than 30% of physicians correctly recommended initiating screening, 47.3% had been screened, in contrast to 54.8% in areas where 70% or more of physicians made correct recommendations. Seventy-one percent of respondents living in regions where less than 30% of physicians advised screening at the recommended frequency were current on screening, in contrast to 79.9% of respondents living in regions where 70% or more of physicians made this recommendation. These differences were statistically significant after adjustment for individual characteristics.ConclusionStrategies to improve colorectal cancer screening recommendations of primary care physicians may improve the use of screening for millions of Americans.